Pengaruh Harga, Produksi, Luas Lahan dan Kurs Dollar Amerika Serikat Terhadap Volume Ekspor Teh Indonesia Serta Daya Saingnya Periode 2000-2012 - Wardani, Ni Wayan Gita; Sudirman, Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 1, Januari 2015 (pp. 1 - 70), 2015)
The purpose of this study was to determine the effect of price, production, land area and the United States dollar exchange rate against the Indonesian tea export volume as well as its competitiveness in the period 2000-2012. This study used a quantitative research is to look at the level of the price of tea, tea production levels, as well as the tea plantation area US dollar exchange rate in the period 2000-2012. The data analysis technique used in this study are revealed comparative advantage index (RCA) and multiple linear regression analysis. It was found that simultaneous price variable (X1), Production (X2), Land Area (X3), and the United States Dollar exchange rate (X4) significant effect on Indonesian tea export volume from 2000 to 2012 period (Y). Partial variable price (X1) has no effect on Indonesian tea export volume from 2000 to 2012 period. Production partial variable (X2) has no effect on Indonesian tea export volume year period 2000-2012. Partial variable Land Area (X3) does not affect the volume of Indonesian tea export period 2000-2012. Partially United States Dollar exchange rate variable (X4) effect on Indonesian tea export volume Period 2000-2012 (Y). Finally, Individually competitiveness of Indonesian tea export volume may be said to have a fairly high competitiveness because the RCA index ? 1.
Keywords: Harga, Produksi, Luas Lahan, Kurs Dollar, Volume Ekspor